Durability Design of Concrete Structures - Sarja, A.; Vesikari, E. (CRC Press, 2014)
"Concrete structures can be designed for durability by applying the principles and procedures of reliability theory combined with traditional structural design. This book is the first systematic attempt to introduce into structural design a general theory of structural reliability and existing calculation models for common degradation processes. It covers both the theoretical background and practical design for service life and includes worked examples which highlight the application of the design procedure and methods."--Provided by publisher.